Laser Treatment of Retinopathy of Prematurity in “Retina Lasers in Ophthalmology: Clinical Insights and Advancements” - Кацан, Сергій Володимирович; Адаховська, Анастасія Олексіївна (Springer International Publishing, 2023)
This book discusses the new era of modern retinal laser therapy and its clinical applications. While the photocoagulation era universally presupposed the therapeutic necessity of laser-induced retinal damage, the modern retinal laser therapy is equally opposed to this idea. The evidence for this sea-change in the understanding of retinal laser is well presented within this book, and the conceptual and clinical consequences are discussed with particular emphasis on the emergence of retinal laser therapy as the first reasonable preventive and restorative intervention for the most important retinal disorders. Finally, the future of modern retinal laser therapy is highlighted with respect to coming technological advances, remaining challenges, and the place of retinal laser in the management of retinal disease. This book is an essential resource for all ophthalmic residents and clinicians seeking a clear and concise guide to modern retinal laser therapy in their everyday practice.
This book discusses the new era of modern retinal laser therapy and its clinical applications. While the photocoagulation era universally presupposed the therapeutic necessity of laser-induced retinal damage, the modern retinal laser therapy is equally opposed to this idea. The evidence for this sea-change in the understanding of retinal laser is well presented within this book, and the conceptual and clinical consequences are discussed with particular emphasis on the emergence of retinal laser therapy as the first reasonable preventive and restorative intervention for the most important retinal disorders. Finally, the future of modern retinal laser therapy is highlighted with respect to coming technological advances, remaining challenges, and the place of retinal laser in the management of retinal disease. This book is an essential resource for all ophthalmic residents and clinicians seeking a clear and concise guide to modern retinal laser therapy in their everyday practice.